The pharmacogenetics of cardiovascular drugs - Stanković Sanja; Ašanin Milika; Majkić-Singh Nada (Journal of Medical Biochemistry, 2014)
This article will primarily summarize the current knowledge of the pharmacogenetics of commonly used drugs for the cardiovascular system: oral anticoagulants, antiplatelet therapy and statins. Coumarin anticoagulants are widely used to treat and prevent thromboembolisms. Variations in the CYP2C9 and VKORC1 genes influence the pharmacodynamic response to coumarins. Genetic variation makes an important contribution to the variation in the response to clopidogrel, the most commonly prescribed antiplatelet treatment. Genetic polymorphisms in the CYP2C19 gene as in the paraoxonase 1 gene are associated with clopidogrel effectiveness and have shown an association with excess of ischemic events such as myocardial infarction and stent thrombosis, but also with serious threat of bleeding. Statin pharmacogenetics has the potential to improve the safety and effectiveness of lipid-lowering therapy by statins. Genetic variations in apolipoprotein E, cholesterol ester transfer protein, kinesin-like protein 6, statin transporter OATP1B1 etc. could partly explain the interindividual variation in statins therapeutic response and adverse reactions. Finally, we comment on the pharmacogenetics of other cardiovascular drugs that have been extensively studied, but for which data are conflicting or that have not yet seen clinical implementation. Based on the available data, it could be expected that in the future genome-tailored drug prescription and use of defined algorithms will contribute to the successful drug action, lowering the frequency of adverse events, and will have greater clinical relevance.